LAS COMPETENCIAS: UNA PROPUESTA CONCEPTUAL HACIA LA UNIFICACIÓN MULTIDIMESIONAL EN EL CONTEXTO DE LOS RECURSOS HUMANOS - Dávalos, Cuahtémoc Guerrero; Vásquez, Germán Aníbal Narváez (European Scientific Journal, ESJ, 2014)
The meaning of the term competition has given rise to multiple interpretations, nuances, or even to misunderstandings, since the concept has more than one meaning, and discernment settling context of the audience at any given time. In a general way it is usually understood that competition comprises the attitudes, knowledge and skills that enable to successfully develop an integrated set of functions and tasks in accordance with the performance criteria considered suitable especially in the workplace. Therefore, this paper aims to show different meanings of the term Competition, in which product content analysis methodology provides a global type definition covers the essential components, in order to have a more accurate understanding; although different scenarios is at stake, given the connotations that make it a term with many meanings, and therefore difficult to conceptualize. To carry out this investigation, we applied the content analysis methodology that is affected by means of encoding, namely, a process in which the relevant characteristics of the contents are transformed into units allowing precise description and analysis. The sample consisted of 59 definitions authors analyzed fifteen categories corresponding to the three concepts that currently manifest in the organizational environment.